2011
DOI: 10.1177/0961203311431249
|View full text |Cite
|
Sign up to set email alerts
|

Urinary monocyte chemoattractant protein 1 and alpha 1 acid glycoprotein as biomarkers of renal disease activity in juvenile-onset systemic lupus erythematosus

Abstract: A higher proportion of patients with juvenile-onset systemic lupus erythematosus (JSLE) will have renal involvement compared with adult-onset disease, some progressing to renal failure in adulthood. Histological examination is the gold standard for diagnosing lupus nephritis (LN), but its invasive nature limits routine use. Using cross-sectional cohort analysis, we aimed to determine whether urinary concentrations of monocyte chemoattractant protein-1 (MCP1), alpha-1-acid glycoprotein (AGP) and interferon-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 17 publications
5
54
0
5
Order By: Relevance
“…Urinary levels of AAG and MCP1 but not interferon-inducible protein 10 were significantly higher in eight active lupus nephritis patients compared with 52 inactive lupus nephritis patients in a study from the UK JSLE Cohort [21]. However, the AAG and MCP1 values overlapped between both of the cSLE groups and healthy controls.…”
Section: Biomarkersmentioning
confidence: 84%
“…Urinary levels of AAG and MCP1 but not interferon-inducible protein 10 were significantly higher in eight active lupus nephritis patients compared with 52 inactive lupus nephritis patients in a study from the UK JSLE Cohort [21]. However, the AAG and MCP1 values overlapped between both of the cSLE groups and healthy controls.…”
Section: Biomarkersmentioning
confidence: 84%
“…Thus, both residual glomerular cells and infiltrating cells may be attributable to the excretion of inflammatory chemokines into urine. However, little information is available regarding the implication of urinary proinflammatory chemokine levels in pediatric-onset renal diseases (Watson et al 2012). So far, it has been reported that the urinary MCP-1 concentration may predict disease activity in adulthood IgAN and LN (Stangou et al 2009(Stangou et al , 2013Abujam et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Since urinary proinflammatory chemokine excretion may reflect histologic inflammatory damage in patients with GN (Stangou et al 2009(Stangou et al , 2013Watson et al 2012;Abujam et al 2013;Korzeniecka-Kozerska et al 2013), measurement of urinary cytokine/chemokine concentrations may lead to the development future non-invasive procedures for prediction of disease activity in patients with GN, rather than the use of invasive renal biopsy (Stangou et al 2009). We also have reported the usefulness of measuring the concentrations of urinary fractalkine and MCP-1 in children with GN, although we did not examine the implications of other reported urinary cytokines/chemokines such as interleukin-6, epidermal growth factor, and interferon-γ-inducible protein 10 (Stangou et al 2009;Abujam et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models, injection of orosomucoid proved to have a protective effect against nephrosis induced by puromycin aminonucleoside (PAN) and suggested that orosomucoid preserves the permeability for albumin in the glomerulus [33]. Urinary orosomucoid had been found to predict the activity of lupus nephritis and higher values were seen in lupus nephritis with active disease than in patients with inactive disease [34]. Highest value of ORM2 was seen in FENS.…”
Section: Discussionmentioning
confidence: 97%